2017
DOI: 10.1371/journal.pone.0187821
|View full text |Cite
|
Sign up to set email alerts
|

Adverse obstetric outcomes in pregnant women with uterine fibroids in China: A multicenter survey involving 112,403 deliveries

Abstract: ObjectiveTo estimate the association between uterine fibroids and adverse obstetric outcomes.MethodsThis was a retrospective cross-sectional study of 112,403 deliveries from 14 provinces and 39 different hospitals in 2011 in mainland China. We compared pregnancy outcomes in women with and without uterine fibroids who underwent detailed second trimester obstetric ultrasonography during 18 to 22 weeks. Obstetric outcomes include cesarean delivery, breech presentation, preterm delivery, placenta previa, placental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
1
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 26 publications
5
52
1
6
Order By: Relevance
“…Finally, 19 articles (18 studies) were included in this meta-analysis. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] One of these papers reported complementary information to the primary outcome information. 35,38 The selection process is shown in Figure 1.…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, 19 articles (18 studies) were included in this meta-analysis. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] One of these papers reported complementary information to the primary outcome information. 35,38 The selection process is shown in Figure 1.…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
“…26,33,35,38,41 There were also 13 case-control studies, including 10 270 pregnant women with UF and 150 795 control women without UF. 24,25,[27][28][29][30][31][32][34][35][36][37]40,42 In all included studies, the presence or absence of UF was determined by ultrasound examination during the first or second trimesters of gestation. Characteristics of the included studies and participants are displayed in Table 1.…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhao et al reported that 2.68% of Chinese pregnant women were identified with at least one fibroid. Red degeneration of uterine fibroids is most frequent around the 20th week of gestation and during puerperium.…”
mentioning
confidence: 99%